The Effect of Repetition Style Using the ordinary and the opposite methods in learning and retaining the snatch in first year students of the physical education college – university of Baghdad - Hashem, Falah (Journal of Physical Education, 2013)
The research consisted of five chapters. The first chapter included the introduction and the importance of the research. Scientific development have reached all fields of sports as well as teachers in the field of sports thus the importance of the study concentrates on using repetition style and finding its effect on learning. The problem of the research lies in studying repetition style for all stages of performance. The aim of the research is to identify the differences in learning snatch in two experimental groups (the ordinary group and opposite group) compared to the controlling group. The second chapter tackled the repetition style, opposite and ordinary learning styles. The third chapter included the procedures. The researcher used the experimental method on first year students of Physical Education College/ university of Baghdad of the academic year 2011 - 2012. The data is arranged and displayed in tables in chapter four. The tables are then discussed and analyzed using proper statistical operations. The fifth chapter included the conclusions and recommendations. The researcher concluded that repetition style achieved great levels of learning the snatch in both experimental groups. Finally the researcher recommended using the opposite style when teaching the acquisition of the snatch skill .